IFNL3 mRNA structure is remodeled by a functional non-coding polymorphism associated with hepatitis C virus clearance - Lu, Yi-Fan (Sci Rep, 2015)
Polymorphisms near the interferon lambda 3 (IFNL3) gene strongly predict clearance of hepatitis C virus (HCV) infection. We analyzed a variant (rs4803217 G/T) located within the IFNL3 mRNA 3′ untranslated region (UTR); the G allele (protective allele) is associated with elevated therapeutic HCV clearance. We show that the IFNL3 3′ UTR represses mRNA translation and the rs4803217 allele modulates the extent of translational regulation. We analyzed the structures of IFNL3 variant mRNAs at nucleotide resolution by SHAPE-MaP. The rs4803217 G allele mRNA forms well-defined 3′ UTR structure while the T allele mRNA is more dynamic. The observed differences between alleles are among the largest possible RNA structural alterations that can be induced by a single nucleotide change and transform the UTR from a single well-defined conformation to one with multiple dynamic interconverting structures. These data illustrate that non-coding genetic variants can have significant functional effects by impacting RNA structure.